2014
DOI: 10.17576/ajag-2013-4-5774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ownership Structure on Malaysian Companies Performance

Abstract: The aim of this paper is to examine effects of managerial and family ownership structure on the company performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Indonesia and Malaysia have a similar condition in ownership structure. A concentrated ownership structure on the controlling shareholders happens in firms in Indonesia (Mutamimah & Hartono, 2010) and Malaysia (Amran & Ahmad, 2013). Commonly, controlling shareholders in Malaysia are state, family, and individual (Amran & Ahmad, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia and Malaysia have a similar condition in ownership structure. A concentrated ownership structure on the controlling shareholders happens in firms in Indonesia (Mutamimah & Hartono, 2010) and Malaysia (Amran & Ahmad, 2013). Commonly, controlling shareholders in Malaysia are state, family, and individual (Amran & Ahmad, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A concentrated ownership structure on the controlling shareholders happens in firms in Indonesia (Mutamimah & Hartono, 2010) and Malaysia (Amran & Ahmad, 2013). Commonly, controlling shareholders in Malaysia are state, family, and individual (Amran & Ahmad, 2013). In Indonesia, controlling shareholders are family or founder having a immense control managers to make a decision (Mutamimah & Hartono, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Using regression analysis, Amran and Ayoib (2013) showed that managerial and family ownership relates significantly to ROA and ROE; and firm performance decreases when the managers' share ownership increases. Furthermore, by employing the common effect robust model, Wahla et al (2012) concluded that managerial ownership has a significant negative relationship with firm performance; concentrated ownership showed insignificant relationship with firm performance; leverage showed a significant negative relationship with firm performance; and insignificant relationship between asset turnover and firm performance.…”
Section: Previous Researchmentioning
confidence: 99%
“…However, the extent of the eISSN: 2357-1330 Selection and peer-review under responsibility of the Organizing Committee 261 alignment is determined by the degree of the ownership (Jusoh & Che-Ahmad, 2014). The greater the MO, the less severe the agency problem (Amran & Che-Ahmad, 2013). However, this could be to the detriment of the minority shareholders.…”
Section: Managerial Ownership (Mo)mentioning
confidence: 99%